Nueva ley de amparo. Excepción al principio de inmutabilidad del acto impugnado en el contencioso administrativo federal - Carmona Calderón, Ma. Constancia (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
The right to effective legal protection enshrines the delivery of complete justice that lies in the pronouncement of all the aspects discussed in the lawsuit. Diputes arising between the Government and the governed are settled in a federal contentious-administrative court. Before rendering any final decision, the Federal Court of Justice for Tax and Administrative Matters, in view of the principle of greater benefit, examines the challenges aimed at controverting the merits of the case. Nevertheless, if the annulment of the contested act is pronounced on grounds of lack or inadequacy of a statement of reasons in respect of the contested order, the defendant is required to issue a new one, correcting it, which always entails conducting another trial to go into the details of the merits of the case. The Amparo Law of 2 April 2013 establishes an exception to the principle of the immutability of an administrative act, requiring the respondant to render a justified report that shall be supported by a statement of reasons concerning the contestesd act, or to complement its inadequacy in those aspects, enabling the possibility of demanding extended warranties. The contested act will be analyzed considering both the supporting statement and the statement of reasons manifested in the report. Should the inconsistency in the judgment persist, the opinion shall be deemed to be flawed and the verdict shall be null and void. If such principle should be implemented in the federal contentious-administrative court and the possibility of extending the lawsuit regarding the supporting statement and the statement of reasons expressed by the authority when producing its reply; or if the lack or inadequacy of such requirement persisted in the analysis of the controverted act performed by the Court, then it would be deemed that the contested decision is flawed, preventintg the respondant to issue a new one. This in turn would result in a greater benefit for the applicant, since it would definitely put an end to the controversy.

El derecho a la tutela jurisdiccional efectiva consagra la impartición de justicia completa que estriba en el pronunciamiento de todos los aspectos debatidos. En el contencioso administrativo federal se dirimen los conflictos que se suscitan entre la administración pública y el gobernado. En el dictado del fallo definitivo, atendiendo al principio de mayor beneficio, el Tribunal Federal de Justicia Fiscal y Administrativa analiza los conceptos de impugnación encaminados a controvertir el fondo del asunto; sin embargo los vicios de falta o insuficiencia de fundamentación y motivación del acto impugnado, trae como consecuencia la declaratoria de nulidad para el efecto de que la demandada emita uno nuevo subsanándolo, lo que conlleva la prosecución de otro juicio que atienda al fondo. La Ley de Amparo vigente a partir del 2 de abril de 2013, establece una excepción al principio de inmutabilidad del acto administrativo, obliga a la responsable a rendir el informe justificado fundando y motivando el acto reclamado o a complementar su insuficiencia en esos aspectos, habilitándose la posibilidad de ampliar la demanda de garantías; el acto reclamado se analizará considerando la fundamentación y motivación que para completarlo se haya expresado en el informe; de subsistir la inconsistencia en la sentencia se estimará que éste presenta un vicio de fondo que impide su reiteración. De implementarse en el contencioso administrativo federal dicho principio y la posibilidad de ampliar la demanda respecto de la fundamentación y motivación que exprese la autoridad al producir su contestación, de subsistir la ausencia o insuficiencia de ese requisito, en el análisis del acto impugnado que realice el Tribunal, estimaría que el acto presenta un vicio de fondo que impida a la demandada emitir otro, lo que redundaría en un mayor beneficio para el justiciable al ponerse fin a la controversia.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2015-0940; Proceso; Contencioso; Ley de amparo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/648